Management of Iatrogenic Ureteral Trauma Post Caesarean Section - Prilian Akbaril Satryo Pamungkas; Besut Daryanto; Andri Kustono (Fakultas Kedokteran Universitas Brawijaya, 2023)
Trauma in the ureter occurs in 1-2.5% of all urogenital trauma, and the most common causes of iatrogenic ureteral trauma come from the Obstetrics Gynecology field (59%). One of the causes of delayed diagnosis of ureteral trauma is the lack of operator awareness. This case report described a 29-year-old woman suspected of ureteral trauma after urine-like fluid was found during a cesarean section operation. After 12 days, a clear-yellowish fluid was obtained from the abdominal drain, so the patient was referred to urologists. The abdominal drain produced fluid approximately 250-300cc/24 hours, clear yellow color. IVP and left RPG inferred left distal ureter laceration AAST grade III. Re-exploration, ureteroneocystostomy using Boari Flap technique, and DJ-Stent insertion were done. On the second day postoperative, the abdominal drain production was < 25cc/24 hours in red color. Ureteral trauma is rare, often unnoticed, and often diagnosed late due to a lack of operator alertness.